2017
DOI: 10.1371/journal.pone.0180037
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitizing indomethacin-conjugated dextran-based micelles for effective delivery of paclitaxel in resistant breast cancer therapy

Abstract: Multidrug resistance (MDR) against chemotherapeutic agents has become the major obstacle to successful cancer therapy and multidrug resistance-associated proteins (MRPs) mediated drug efflux is the key factor for MDR. Indomethacin (IND), one of the non-steroidal anti-inflammatory agents, has been demonstrated to increase cytotoxic effects of anti-tumor agents as MRP substrates. In this study, dextran-g-indomethacin (DEX-IND) polymeric micelles were designed to delivery paclitaxel (PTX) for the treatment of MDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Internalization of DEX-SS-IND/PTX micelles by MCF-7 and MCF-7/PTX cells was quantitatively investigated via determining intracellular PTX concentration by HPLC method [ 19 ]. 5 × 10 4 cells/well of cells were cultured in a 24-well plate and kept at 37°C for 24 h. Then, PTX, PTX + IND, DEX-IND/PTX, and DEX-SS-IND/PTX micelles were added and incubated for 6 and 24 h, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Internalization of DEX-SS-IND/PTX micelles by MCF-7 and MCF-7/PTX cells was quantitatively investigated via determining intracellular PTX concentration by HPLC method [ 19 ]. 5 × 10 4 cells/well of cells were cultured in a 24-well plate and kept at 37°C for 24 h. Then, PTX, PTX + IND, DEX-IND/PTX, and DEX-SS-IND/PTX micelles were added and incubated for 6 and 24 h, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular PTX content was expressed as the amount (nmol) of PTX associated with a unit weight (1 mg) of cellular protein. Protein contents of cell lysate were measured using BCA protein assay reagent kit [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in different dosing schedules. It should be noted, however, that the cumulative dose of paclitaxel used here is in the range of what is used to treat tumors in mice [14; 32; 34]. In addition to general analysis of potential toxic side effects, the potential interference of ESI-09 treatment with the anti-cancer effect of treatment needs to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that indomethacin can effectively restore TRIAL sensitivity in melanoma cells and act by upregulation of death receptor 5 (DR5) and/or downregulation of survivin [ 28 ]. In the last few years, intensive research has also been conducted on the possibilities of using indomethacin in the treatment of castration-resistant prostate cancer [ 29 ] and its formulations in hormone-refractory breast cancer [ 30 , 31 ].…”
Section: Therapeutic Activity Of Indomethacin and Its Mechanism Ofmentioning
confidence: 99%